PERAN KELOMPOK TANI DALAM PENERAPAN SRI (SYSTEM OF RICE INTENSIFICATION) DI KECAMATAN KALIKAJAR KABUPATEN WONOSOBO - Chindra Yenni Wastika; Sunarru Samsi Hariadi; Subejo Subejo (Agro Ekonomi, 2014)
This research was conducted in Kalikajar Sub District Wonosobo Regency. The purpose of this research were to understand how far the role of farmer group in the application of SRI (System of Rice Intensification), influencing the factors in the role of farmer group in SRI application, and to understand the influence of the farmer group’s role in the SRI application in Kalikajar Sub Wonosobo Regency. The method were used in this research was descriptive analysis. The data were analyzed by proportion test, multiple linear regression analysis and simple linear regression analysis.The result of this research showed that more than 50% at sample evaluated that using rates the role of farmer group in high category. Farmer’s attitude and the role of extension agents positively affected to the role of farmer group in SRI application. The farmer’s level of education, land scale, farmer’s experience, frequence of the attendance, and the role of farmer group’s leader have no affect in the role of farmer group in SRI application. The role of farmer group as learning media, cooperation media, and production unit has positively affected to SRI application in Kalikajar Sub District Wonosobo Regency which means the application of SRI increased as the increased of the role farmer group.